Clinical Factors Associated With Patterns of Medication Errors Among Pediatric Hospitalized Patients in Northwest Ethiopia: A Multicenter Prospective Observational Study. - Moges, Tilaye Arega; Dagnew, Fisseha Nigussie; Tarekegn, Getachew Yitayew; Wondm, Samuel Agegnew; Zewdu, Woretaw Sisay; Anberbr, Sisay Sitotaw; Nigussie, Habtamu; Dagnew, Samuel Berihun; Klug, Yoel A. (BioMed Research International, 2026)
Background: Medication safety is an important public health challenge, especially in pediatrics. Medication errors (MEs) are often underreported in pediatrics and can lead to adverse outcomes such as frequent readmissions, increased total healthcare costs, prolonged hospitalization, and related morbidity and mortality. Thus, this study is aimed at assessing the magnitude and determinants of MEs among pediatric hospitalized patients at comprehensive specialized hospitals in Northwest Ethiopia. Methods: A multicenter prospective observational study involving pediatric hospitalized patients was conducted over 4 months, utilizing systematic random sampling for participant selection. Three clinical pharmacists, after a day of training, collected data under the supervision of an MSc health professional, with support from pediatricians in each hospital for reviewing MEs and adjusting treatment plans. Pediatric patients were followed prospectively during their hospital stay from admission to discharge. Data collection occurred via the Kobo Toolbox platform and was analyzed with STATA Version 17.0. Both bivariate and multivariable logistic regression analyses identified factors related to MEs, with statistical significance set at a p value < 0.05. Results: Among 358 pediatric hospitalized patients, 53.63% experienced at least one ME, totaling 254 identified errors. The prescribing stage accounted for the highest percentage of errors (40.16%), followed by the administration stage (32.68%). The predominant types of MEs were dose errors (30.31%), frequency errors (14.96%), and omission errors (14.17%). Multivariable logistic regression analysis revealed that polypharmacy (≥ 5 medications) (AOR = 2.005, 95% CI: 1.269–3.168), male sex (AOR = 1.707, 95% CI: 1.097–2.656), and prolonged hospital stay (AOR = 1.673, 95% CI: 1.076–2.602) were significantly associated with the occurrence of MEs. Conclusion: This study found that MEs were prevalent in pediatric hospitalized patients. Polypharmacy, male patients, and the length of hospital stay were independent predictors of MEs. To reduce MEs, computer‐based prescribing practice and clinical pharmacy services should be routine practices in the study settings.